KONSEP PENGATURAN PARIWISATA HALAL DI ACEH - Ilka Sandela; Nila Trisna; Phoenna Ath Thariq (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Halal tourism is a tourism that in its implementation fulfill the provisions of Islamic law. In the implementation of halal tourism, a special regulation is needed so that the implementation can be guaranteed as expected. The purpose of this research was to examine the substance of Qanun Aceh Number 8 of 2013 concerning Tourism, whether it contains elements of halal tourism or not and how far the regulation is. Then, it will be reviewed the concept of halal tourism regulation that are ideally applied in Aceh Province. The research method used is normative juridical research method. The results showed that explicitly there is no term halal tourism in Qanun Aceh Number 8 of 2013 concerning Tourism, but in substance there are some provisions that contain the values of halal tourism, among others the function of tourism, the direction of research and development of tourism in Aceh, tourism business, values that must be considered in the business of objects and tourist attractions, obligations of tourism object businesses , obligations of star hotel managers, provisions for restaurant managers, restrictions on tourist attractions, and provisions that must be met for foreign tourists. However, the existing provisions have not been able to accommodate the implementation of halal tourism optimally. The ideal concept of halal tourism regulation should contain in detail the basic elements and objectives of halal tourism implementation, classification of halal tourism destinations, standards of each type of halal tourism destination, halal tourism certification, promotion and marketing, supervision, and sanctions. It is recommended to establish special legislation on halal tourism in Aceh either in the form of other qanun or in the form of governor regulation, the purpose of which is to become guidelines and reference of halal tourism standards in all regions in Aceh Province, so that the implementation of halal tourism can be carried out opptimally.